Analysis of the Influence of Brand Image and Online Promotion on the Purchase Decision of Kopi Kenangan Products by Generation Z at Kopi Kenangan Sulawesi Surabaya - Ramadhan, Akmal Nugraha; Setyadi, Taufik; Rizkiyah, Noor (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
This study investigates the impact of brand image and online promotion on the purchasing decisions of Generation Z consumers at the Kopi Kenangan branch located in Sulawesi, Surabaya. Utilizing a quantitative research approach, data were collected from 100 respondents aged 20